(untitled) (Sebha University Conference Proceedings, 2024)
Our study aimed to find out the reality of the use and application of block chain technology in the global and Arab banking sectors, and to measure the extent of confidence and acceptance of banks and their customers within the global environment in general and the Arab environment in particular, to adopt block chain technology in the banking field, and to know its impact on developing platforms Digital and banking performance enhancement, In our research paper, we relied on the descriptive analytical approach, as we based the descriptive approach through the theoretical literature of block chain technology, banking performance, and performance enhancement, As for the analytical approach, we dealt with the reality of adopting block chain technology in some global and Arab banking systems as a model based on basic information and data for some international and Arab banks as a model in light of information and communication technologies, And in light of the experiences of some international and Arab banks that have adopted this technology, Our study has found that block chain technology represents the ideal solution in developing and improving banking services provided to customers in terms of security, transparency, speed, operational cost reduction and decentralization, Improving capital, and enhancing the operational efficiency of banks, And it has a positive impact on achieving sustainability and continuity and keeping banks in competition with the developments of international banks as a result of increasing profits and ease of entry to local and international markets and saving time and effort, And the use of block chain technology in banks has a positive impact on evaluating financial performance and achieving a competitive advantage to achieve the bank’s goals of raising its profits. And reduce manual procedures and contribute to meeting the needs of the financial and banking sector by eliminating intermediaries.